ANALISIS PENGARUH MEDIA INTERNET TERHADAP PERILAKU PENYIMPANGAN SEKSUAL PADA REMAJA DI SMP NEGERI 4 TEBING TINGGI - Maximilianus Dasril Samura; Cempaka Sari (JURNAL ILMIAH DHDT - KEBIDANAN, 2019)
The progress of the application of internet media technology among teenagers makes teenagersspend a lot of time useless, so that few teenagers have experience changes in communication,ethics, and behavior, even increasing sexual deviance behavior. The purpose of this study was todetermine the effect of internet media on sexual deviance behavior in adolescents of SMP Negeri 4Tebing Tinggi in 2019. This type of research uses a cross-sectional method. The population in thisstudy was 90 students. The results show that there is an influence on the frequency of internetmedia usage on adolescent sexual deviation behavior. There is an effect of the duration of internetmedia usage on adolescent sexual deviation behavior. There is the influence of internet mediaaccess used on adolescent sexual deviation behavior, and the variable that most influences thebehavior of adolescent sexual deviation is the variable frequency of using internet media withprevalency ratio 3.501. It expected that adolescents do not use the facilities and internet mediatheir have for pornography. Besides, teenagers should be positive things in their spare time, suchas taking school extracurricular activities, exercising, or did good hobbies to avoid deviantbehavior.